2017
DOI: 10.18311/ajprhc/2017/15834
|View full text |Cite
|
Sign up to set email alerts
|

A Study to Assess the Effectiveness of Hand Hygiene Technique among School Children in Maharashtra, India

Abstract: Keeping kids healthy and clean it is important to teach the basic personal hygiene. It is extremely effective and inexpensive way to prevention of diarrhea and acute respiratory infections. The aim was to assess the effectiveness of hand hygiene technique demonstration on hand hygiene practices of primary school going children. Data was collected from the Rotary Shikshan Santha Malkapur Karad, Maharashtra, India. The study design used was one group pre-test, post-test design. 60 primary school going children a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
3
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 3 publications
1
3
0
1
Order By: Relevance
“…The considerably higher frequency of handwashing before meals among the children in the present study may be due to the Indian cultural tradition and ceremonial practice of washing hands before meals or the desire for clean, fresh hands before eating. Similar findings were found in studies conducted in Colombia [6] and India [3,[7][8] which reported that 82.5% and 86.4% of the children, respectively, wash their hands after using the toilet.…”
Section: Practice Basedsupporting
confidence: 89%
See 3 more Smart Citations
“…The considerably higher frequency of handwashing before meals among the children in the present study may be due to the Indian cultural tradition and ceremonial practice of washing hands before meals or the desire for clean, fresh hands before eating. Similar findings were found in studies conducted in Colombia [6] and India [3,[7][8] which reported that 82.5% and 86.4% of the children, respectively, wash their hands after using the toilet.…”
Section: Practice Basedsupporting
confidence: 89%
“…The foundations of lifelong responsibility for the maintenance of personal hygiene are laid down in childhood, which is important for a healthy childhood, for a healthy adulthood, and for the development of positive values about health and the use of health services. [3,6,7] The children residing in the sheltered homes showed a positive behavior change after the educational intervention. Table 5 showed that 82.65% of the participants who were using water only for washing their hand started using hand washing solution post intervention.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…Menurut beberapa ahli, ada beberapa metode dan media yang dilakukan secara simultan berpengaruh secara efektif dalam penyampaian pesan kesehatan dan mempengaruhi perubahan pengetahuan dan perilaku. Metode tersebut antara lain metode ceramah, metode diskusi, demonstrasi dan simulasi (Tidwell et al, 2020;Kobra et al, 2016;So et al, 2019;Sumitro et al, 2019;Mane & Tata, 2017). Ceramah adalah suatu cara dalam menyampaikan pesan, paparan mengenai kesehatan secara lisan kepada kelompok sasaran (Sumitro et al, 2019;Avissa et al, 2015).…”
Section: Pendahuluanunclassified